Differences in Caregiver‐Reported Health Problems and Health Care Use in Maltreated Adolescents and a Comparison Group From the Same Urban Environment. Issue 1 (30th December 2014) - Schneiderman, Janet U.; Kools, Susan; Negriff, Sonya; Smith, Sharon; Trickett, Penelope K.
Abstract Maltreated youth have a high prevalence of acute and chronic mental and physical health problems, but it is not clear whether these problems are related to maltreatment or to a disadvantaged environment. To compare health status and health care use of maltreated youth who had an open case with child protective services to comparison youth living in the same community, we conducted a secondary analysis of caregiver reports for 207 maltreated adolescents (mean age 11.9 years) and 142 comparison adolescents (mean age 12.3 years) living in urban Los Angeles, using questionnaire data from a larger longitudinal study framed in a socio‐ecological model. Caregivers included biological parents, relatives, and unrelated caregivers. Analyses included t‐test, MANOVA, chi‐square, and multivariable logistic regression. Caregivers reported similar rates of physical health problems but more mental health problems and psychotropic medicine use in maltreated youth than in the comparison youth, suggesting that maltreated youths' higher rates of mental health problems could not be attributed to the disadvantaged environment. Although there were no differences in health insurance coverage, maltreated youth received preventive medical care more often than comparison youth. For all youth, having Medicaid improved their odds of receiving preventive health and dental care. Attention to mental health issues in maltreated adolescents remains important. Acceptance of Medicaid by neighborhood‐based and/or school‐based services in low‐income communities may reduce barriers to preventive care. © 2014 Wiley Periodicals, Inc.